Differential Associations between CDH13 Genotypes, Adiponectin Levels, and Circulating Levels of Cellular Adhesive Molecules. (27th October 2015) - Teng, Ming-Sheng; Wu, Semon; Hsu, Lung-An; Chou, Hsin-Hua; Ko, Yu-Lin
Abstract : CDH13 gene variants with lower adiponectin levels are paradoxically associated with a more favorable metabolic profile. We investigated the statistical association between CDH13 locus variants and adiponectin levels by examining 12 circulating inflammation marker levels and adiposity status in 530 Han Chinese people in Taiwan. After adjustments for clinical covariates, adiponectin levels were positively associated with soluble vascular cell adhesion molecule-1 (sVCAM1) levels and negatively associated with adiposity status and levels of C-reactive protein (CRP), soluble E-selectin (sE-selectin), and soluble intercellular adhesion molecule-1 (sICAM1). In addition, minor alleles of the CDH13 rs12051272 polymorphism were found to have lower adiponectin levels and higher CRP, sE-selectin, sICAM1, and sVCAM1 levels as well as higher body mass indices and waist circumferences in participants (all P < 0.05 ). In a subgroup analysis stratified by sex, significant associations between CDH13 genotypes and sE-selectin levels occurred only in men (P = 3.9 × 10 - 4 and interaction P = 0.005 ). CDH13 locus variants and adiponectin levels are associated with circulating levels of cellular adhesion molecules and adiposity status in a differential manner that interacts with sex. These results provide further evidence for the crucial role of adiponectin levels and CDH13 gene variants in immune-mediated and inflammatory diseases.